2014
DOI: 10.1017/aee.2015.7
|View full text |Cite
|
Sign up to set email alerts
|

How Academics in Undergraduate Business Programs at an Australian University View Sustainability

Abstract: This article explores conceptualisations of sustainability and perceptions of its importance in curriculum held by business subject and program leaders. Results are reported from an empirical study of the first-year Bachelor of Business program at an Australian university. Research data was collected in 16 semi-structured, in-depth interviews with subject and program leaders over two teaching periods in 2011. Interview transcripts were analysed through the identification of key themes. The results reveal that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Evidence from this research project and recent studies [144,[151][152][153][154][155] indicate SE is still not implemented systematically, with academics adopting a "free-choice" approach to sustainability in their courses. Academics around the world are key "gatekeepers" for implementing SE in their courses, and their teaching practice often reflects personal sustainability orientations/values, internal motivations, and capabilities [151,[156][157][158][159][160]. Teaching practices are further constrained by external limitations implied/applied by their faculty [56], the institution, disciplinary traditions [161][162][163], professional bodies [156,160,164], government agencies, and/or sector level organisations [165].…”
Section: Challenges To Implementing Se In He (Context Of Contexts)mentioning
confidence: 99%
“…Evidence from this research project and recent studies [144,[151][152][153][154][155] indicate SE is still not implemented systematically, with academics adopting a "free-choice" approach to sustainability in their courses. Academics around the world are key "gatekeepers" for implementing SE in their courses, and their teaching practice often reflects personal sustainability orientations/values, internal motivations, and capabilities [151,[156][157][158][159][160]. Teaching practices are further constrained by external limitations implied/applied by their faculty [56], the institution, disciplinary traditions [161][162][163], professional bodies [156,160,164], government agencies, and/or sector level organisations [165].…”
Section: Challenges To Implementing Se In He (Context Of Contexts)mentioning
confidence: 99%
“…Level 3 review from different peer sources was sought at the time of the original initiative. Evidence of level 3 peer review includes a number of peerreviewed publications ( von der Heidt, 2012a( von der Heidt, , 2012b( von der Heidt, , 2013( von der Heidt, , 2014von der Heidt and Lamberton, 2015;von der Heidt and Quazi, 2013 ), by senior teaching and learning academics and by the University Vice Chancellor, who awarded a citation "for a scholarly driven approach to improving learning-centred curriculum design in first-year marketing " (Southern Cross University, 2011) . For SoTL work in Marketing Principles as a member of the Education for Sustainability in the Bachelor of Business Team the author was awarded a national, competitive Office of Learning and Teaching (OLT) Australia award for outstanding contribution to student learning "for a scholarly-driven, team-based approach that transforms the undergraduate business curriculum through education for sustainability " (Office of Learning and Teaching, 2014) .…”
Section: Chinese Australianmentioning
confidence: 99%
“…Researchers have identified a growing debate concerning the role of management education for sustainable development (Adomßent et al, 2014; Kelley & Nahser, 2014; Khurana, 2010; Pfeffer & Fong, 2002; Starkey & Tempest, 2008). Although there is currently no strong theoretical underpinning of sustainability in higher education research (Figueiró & Raufflet, 2015; Stephens & Graham, 2010), there is a large number of empirical and descriptive studies that investigate the conceptualisation of sustainability in higher education, including academics’ understanding of sustainability, the integration of sustainability into the curricula, as well as studies that investigate the impact of sustainability initiatives (for a review, see von der Heidt & Lamberton, 2014). Reid and Petocz (2006), for example, identified three approaches to teaching sustainability, namely (1) the disparate approach in which teaching and sustainability are regarded as two separate entities, (2) the overlapping approach where specific ideas such as environmental or cultural sustainability are incorporated in a subject, and (3) the integrated approach in which sustainability is an essential component of teaching.…”
Section: Sustainability In Management Educationmentioning
confidence: 99%
“…Research by Figueiró and Raufflet (2015) identified similar challenges to the inclusion of sustainability into higher education management curricula: organisational, capability, terminological, and pedagogical. It has also been claimed that business schools have fallen behind other disciplines in introducing sustainability into their curricula (von der Heidt & Lamberton, 2014), and other researchers have identified the need for more research into the extent to which there is consistent integration of sustainability into management curricula (Godemann, Haertle, Herzig, & Moon, 2014).…”
Section: Sustainability In Management Educationmentioning
confidence: 99%